Influence of Drug Abuse by Parents on the Academic Performance of their Children and its Cost Implication on the Nigerian Economy - Azi, Augustine Sambo; Mugu, Juliana Yusufu (NIU Journal of Humanities, 2019)
This study examined the influence of drug abuse by parents on the academic performance of their children in school and its cost implication on the Nigerian economy. The study, which was a theoretical paper, examined the influence of drug addicted parents on their children’s academic performance. It also assessed its cost implication on the Nigerian economy. The study found out that children of drug addicted parents tend to perform poorly academically due to lack of care and attention by their parents. The study also discovered that drug abuse affects a country’s economy negatively. For instance, Nigerians spent N34 billion on drug abuse in year 2013, this has a negative influence on the country’s GDP and economy generally. For this to be mitigated, it was recommended among others that parents being role models of their children, should avoid drug abuse, in addition, government at all levels should enlighten its citizens on the dangers of drug abuse on their health, children and the economy. Key words: Drug abuse, parents, children, academic performance, economy